Sexual behaviour among male methamphetamine and heroin dependents in selected areas in Malaysia - Isa, M.F.M.; Guan, N.C.; Abd Rashid, Rusdi; Habil, Mohd Hussain; Sidi, H.; Said, M.A.; Sulaiman, Ahmad Hatim (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study aims to describe the pattern of sexual behaviour among methamphetamine and heroin users. It describes the pattern of sexual behaviour based on aspects of sex such as desire, interest, drive and obsession in relation to the drug use. A cross-sectional study was carried out among attendees of drug rehabilitation programmes in Kota Kinabalu, Kota Bharu and Kuala Lumpur. All subjects were living in the community with satisfactory psychosocial functioning. This study was primarily based on a validated sexual behaviour self-rated questionnaire followed by face-to-face interview. A total of 227 subjects were included with 124 (54.6) using methamphetamine while 103 (45.4) using heroin. Majority (218; 96) were heterosexuals with 104 (45.8) reported having been involved in high risk sexual behaviour. More methamphetamine than heroin subjects agreed that their sexual thoughts, feelings and behaviours were often associated with the drug (p<0.05). Methamphetamine subjects agreed that the use of methamphetamine caused them to be more obsessed with sex and they found themselves to be preoccupied with sexual thoughts while being under the influence of the drug (p<0.05). Heroin subjects mainly reported on negative effects of the drug on their sexual behaviour. Methamphetamine subjects reported that the use of drug had positively affected their sexual interest and drive (p<0.05). Methamphetamine subjects were also 1.97 times more likely than heroin subjects to be involved in risky sexual behaviour. The results of this study can be utilized to improve the drug treatment and rehabilitation programme. Methamphetamine subjects were more likely than heroin subjects to be involved in risky sexual behaviour.